A comparison of empirical equations of Estimating Potential Evapotranspiration (PET) from climatological data in Erbil city - Sardar.M.R.K Al-Jumur (Zanco Journal of Pure and Applied Sciences, 2020)
Potential evapotranspiration (PET) is an important index of hydrologic budgets at different spatial scales and it is a critical variable for understanding regional hydrological processes. The objective of this study is to find the most suitable method for estimating PET in Erbil city which was done by comparing seven commonly PET methods. Radiation based method: Pristley –Taylor(PT), Turc(TU), Makkink (MK), and temperature based method: Ivanov (IV), Penman–Monteith method (1965) , FAO Penman–Monteith method, and Thornthwaite(TW). The data were collected and used in the models to find PET for the period (1992-2015). The performance indicators were applied by using statistical parameters such as: the Root Mean Square Error (RMSE), Mean Absolute Error (MAE), person correlation coefficient (R2), MBE Mean bias error. The monthly PET results from the models were compared with the actual evaporation. Current work shows that Makkink (MK) model is better than the other models for estimating the potential Evapotranspiration in Erbil depending on the values of statistical parameters.